Karakteristik Fisika dan Mekanika Papan Partikel dari Limbah Serbuk Gergaji Meranti Merah (Shorea leprosula): Effect of Board Thickness on The Physical and Mechanical Properties of Particleboard Made from Red Meranti (Shorea leprosula) Sawdust Waste - Nona, Risna; Nurmarini, Eva; Fadilla, Ferdi Alim; Kutana, Agung Nugrawan (PERENNIAL, 2025)
The wood processing industry produces red meranti (Shorea leprosula) sawdust waste. This waste is generally not optimally utilized and can have negative impact. The use of sawdust as a raw material for particleboard is an environmentally friendly and economically valuable solution, given that particleboard has the potential to replace solid wood in the wood industry. This study aims to utilize red meranti sawdust waste as raw material for particleboard production using urea formaldehyde adhesive with different particleboard thicknesses. This studi evaluates the effect of thickness variations (1 cm, 1.5 cm, and 2 cm) on the physical properties (moisture content, density, and thickness swelling) and mechanical properties (elasticity/MoE, breaking strength/MoR, and tensile strenth) of particleboard. The results of testing the physical properties of particleboards showed that the average moisture content ranged from 10.92 % to 11.76 %, the density ranged from 0.54 g/cm3 to 0.6 g/cm3, and the thickness swelling ranged from 4.05 % to 12.02 %. Mechanical property testing of particleboard showed that the average MoE ranged from 9,110 kg/cm2 to 67,813 kg/cm2, MoR ranged from 9.44 kg/cm2 to 37.93 kg/cm2, and internal bonding ranged from 0.292 kg/cm2 to 0.396 kg/cm2. Based on the results of statistical analysis, it shows that in testing physical properties, thickness variation does not affect moisture content and density, but affects the thickness swelling of particleboards after being immersed for 2 and 24 hours. In mechanical property testing, thickness variation did not affect internal bonding, but it did affect MoE and MoR. Overall, this study confirms the potential of red meranti sawdust waste as a raw material for particleboard, although improvements are needed in increasing mechanical strength, particularly MoR and internal bonding.